'A problematic plum pit in the piping': a case of traumatic oesophageal perforation. (14th March 2016) - Ibrahim, Nader; Chauhan, Ishaan; Nikkar-Esfahani, Ali
Abstract : A 75-year-old man presented to accident and emergency having swallowed a plum pit. He initially experienced sharp neck pain, which was mild at presentation. He was otherwise haemodynamically stable and was able to subsequently eat a sandwich without consequence. He was referred to the ear, nose and throat senior house office (SHO), who reviewed the soft tissue radiograph, which appeared normal. The patient displayed no concerning clinical signs and was well; however, his pain persisted. Examination revealed a localised area of surgical emphysema on the left side of the neck. Retrospective review of the soft tissue radiograph showed a small region of subcutaneous free air. An urgent CT scan confirmed a pneumomediastinum indicative of an oesophageal perforation. The patient was admitted for observation, and was managed conservatively without surgical intervention. He was weaned onto sterile fluid and progressed to a solid diet. He was discharged from hospital with no long-term sequelae.